HUBUNGAN ANTARA UNDERPRICING DENGAN NILAI SEASONED EQUITY OFFERING (SEO) PERTAMA PERUSAHAAN-PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Hermin Endratno (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2010)
This research aims at knowing the positive average abnormal return and the relationship of the underpricing and the value of the first Seasoned Equity Offering (SEO) towards go public-companies in Indonesia Stock Exchange during three-day-trade after the first emission of underpricing. The data consisted of 12 (twelve) go public-companies in Indonesia Stock Exchange since 1995 and have done their first SEO in 2007. The analysis of data was conducted through test and correlation using Pearson Product Moment statistic model. After the first three days of Initial Public Offering (IPO), the abnormal return was negative. It was shown by the average abnormal return of the first day approximately -0.0088, of the second day -0.0041, and of the third day -0.076. The positive abnormal return, based on the statistic analysis, was insignificantly found either within three-day-trade in the first emission of the underpricing. The insignificant result also occurred to the relationship of the underpricing and the value of the first SEO after the correlation analysis was done. These findings have significant implications for the investors to consider the changes of share prices after the first SEO. It also appears that the factors of underpricing and negative abnormal return should be observed by the emitens to minimize the risks after the IPO. Key words: Underpricing, Seasoned Equity Offering, emission